HUBUNGAN PERSEPSI ETIKA PROFESI DENGAN PERILAKU KERJA PMIK DPD PORMIKI DKI JAKARTA - nom, Ersa Shamira A; Temesvari, Nauri Anggita (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: Perceptions of ethics and work behavior are two things that cannot be separated because perceptions of ethics influence the work behavior of the medical recording profession so that medical recorders can run well. The aim of this research is to determine the relationship between perceptions of professional ethics and the behavior of medical recorders and health information in DPD PORMIKI DKI Jakarta.  The sample consisted of 91 people using quota sampling. Analysis uses the Spearman Correlation Test. The research results show that PMIK's work behavior has a minimum value of 54 and a maximum of 80, mean +/std.deviation 69.76+/7.473 and 95% CI lower-upper 68.20-71.31 and perception of professional ethics a minimum value of 30 and a maximum of 52 , mean+/-std.deviation 45.68+/5.938 and 95%CI lower-upper 44.44- 46.92, r results (0.290) level of strength is sufficient, the positive correlation coefficient value of the relationship between the two variables is said to be in the same direction and the p-value 0.005, the relationship between variables is significant, there is a relationship between perceptions of professional ethics and PMIK work behavior. Training facilities for work ethics and behavior, internal research on perceptions and collaboration with educational institutions. Keywords: Medical Recorder and Health Information, Work Behavior, Perception of                  Professional Ethics Abstrak: Persepsi etika dengan perilaku kerja merupakan dua hal yang tidak dapat dipisahkan karena persepsi etika mempengaruhi perilaku kerja dari profesi perekam medis sehingga perekam medis bisa menjalankan tugasnya dengan baik. Tujuan dari penelitian ini adalah untuk mengetahui hubungan persepsi etika profesi dengan perilaku perekam medis dan informasi kesehatan di DPD PORMIKI DKI Jakarta.  Sampel terdiri dari 91 orang menggunakan kuota sampling. Analisis menggunakan Uji Korelasi Spearman. Hasil penelitian menunjukkan bahwa perilaku kerja PMIK nilai minimum 54 dan maximum 80, mean +/std.deviasi 69,76+/7,473 dan 95%CI lower-upper 68,20-71,31 dan persepsi etika profesi nilai minimum 30 dan maximum 52, mean+/-std.deviasi 45,68+/5,938 dan 95%CI lower-upper 44,44- 46,92, hasil r (0,290) tingkat kekuatan cukup, bernilai koefisien korelasi positif  hubungan kedua variabel dikatakan searah dan p-value 0,005 hubungan antar variabel bernilai signifikan ada hubungan antara persepsi etika profesi dengan perilaku kerja PMIK. Saran pelatihan etika dan perilaku kerja, penelitian internal tentang persepsi dan kolaborasi dengan institusi pendidikan. Kata kunci: Perekam Medis dan Informasi Kesehatan, Perilaku Kerja, Persepsi Etika Profesi